Field sampling of indoor bioaerosols. Issue 5 (3rd May 2020) - Cox, Jennie; Mbareche, Hamza; Lindsley, William G.; Duchaine, Caroline
Abstract: Because bioaerosols are related to adverse health effects in exposed humans and indoor environments represent a unique framework of exposure, concerns about indoor bioaerosols have risen over recent years. One of the major issues in indoor bioaerosol research is the lack of standardization in the methodology, from air sampling strategies and sample treatment to the analytical methods applied. The main characteristics to consider in the choice of indoor sampling methods for bioaerosols are the sampler performance, the representativeness of the sampling, and the concordance with the analytical methods to be used. The selection of bioaerosol collection methods is directly dependent on the analytical methods, which are chosen to answer specific questions raised while designing a study for exposure assessment. In this review, the authors present current practices in the analytical methods and the sampling strategies, with specificity for each type of microbe (fungi, bacteria, archaea and viruses). In addition, common problems and errors to be avoided are discussed. Based on this work, recommendations are made for future efforts towards the development of viable bioaerosol samplers, standards for bioaerosol exposure limits, and making association studies to optimize the use of the big data provided by high-throughput sequencing methods. Copyright © 2020 American Association for Aerosol Research